Enhancing Cushing’s disease diagnosis: exploring the impact of desmopressin on ACTH gradient during BIPSS - Almeida, Tobias Skrebsky de; Rodrigues, Ticiana da Costa; Costenaro, Fabíola; Scaffaro, Leandro Armani; Farenzena, Maurício; Gastaldo, Fernando; Czepielewski, Mauro Antônio (Frontiers in Endocrinology, 2023)
Introduction The differential diagnosis between Cushing’s disease (CD) and ectopic ACTH syndrome (EAS) is complex, and bilateral inferior petrosal sinus sampling (BIPSS) is considered the gold-standard test. However, BIPSS with corticotropin-releasing hormone (CRH) stimulation is rarely available. Objective This retrospective cohort study aimed to assess the accuracy of the inferior petrosal sinus to peripheral ACTH gradient (IPS:P) before and after desmopressin stimulation for the differential diagnosis of ACTH-dependent Cushing’s syndrome (CS), applying different cutoff values. Methods A total of 50 patients (48 with CD and 2 with EAS) who underwent BIPSS were included in this study. The sensitivity and specificity of IPS:P in BIPSS before and after desmopressin stimulation were evaluated. Various cutoff values for IPS:P were examined to determine their diagnostic accuracy. Results Using the traditional IPS:P cutoff, the sensitivity was 85.1% before stimulation, 89.6% after stimulation, and a combined sensitivity of 91.7%. Applying cutoff values of IPS:P >1.4 before and >2.8 after stimulation, the sensitivity was 87.2% and 89.6%, respectively, with a combined sensitivity of 91.7%. Receiver operating characteristic (ROC) curve analysis determined optimal cutoff values of 1.2 before stimulation and 1.57 after stimulation, resulting in a sensitivity of 93.6% and 93.8%, respectively, with a combined sensitivity of 97.9%. Specificity remained at 100% throughout all analyses. Among the 43 patients who responded positively to stimulation, 42 (97.7%) did so within the first three minutes, and all 43 (100%) did so within the first five minutes. None of the assessed clinical variables predicted the ACTH response to stimulation in BIPSS with statistical significance. Discussion ACTH stimulation with desmopressin during BIPSS improves the accuracy of IPS:P, making it a valuable tool for investigating ACTH-dependent Cushing’s syndrome. Considering the low risk of complications, we recommend the use of desmopressin stimulation during BIPSS for the differential diagnosis of ACTH-dependent CS.